2007
DOI: 10.1258/026835507779700662
|View full text |Cite
|
Sign up to set email alerts
|

Rapid healing of chronic venous ulcers following ultrasound-guided foam sclerotherapy

Abstract: Venous ulcers in patients with serve venous insufficiency responded quickly to UGFS. Long-term follow-up will be important to determine the sustainability of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Frullini and Cavezzi showed foam sclerotherapy is equally applicable in complicated and uncomplicated venous disease (19). Rapid healing of ulcers following foam sclerotherapy was reported in some clinical researches and it confirmed that this treatment could probably achieve the same outcomes that result from saphenous obliteration in leg ulcer patients (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 85%
“…Frullini and Cavezzi showed foam sclerotherapy is equally applicable in complicated and uncomplicated venous disease (19). Rapid healing of ulcers following foam sclerotherapy was reported in some clinical researches and it confirmed that this treatment could probably achieve the same outcomes that result from saphenous obliteration in leg ulcer patients (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 85%
“…This study showed no evidence that foam sclerotherapy speeds ulcer healing [39]. In a second small study, 13 venous ulcers were treated with ultrasound-guided foam sclerotherapy; at 1-week follow-up, two ulcers were healed and significant improvement in ulcer dimension and size was demonstrated [40]. Further research is needed to determine the long-term efficacy of foam sclerotherapy in treating venous ulcers.…”
Section: Subfacial Endoscopic Perforating Vein Surgerymentioning
confidence: 83%
“…[38][39][40][41][42][43][44] Sclerotherapy of varices in the region of venous ulcers improves the healing rate. [45][46][47][48] (GRADE 1B). Recently catheter-directed foam sclerotherapy for chronic venous leg ulcers showed a good healing rate in a prospective case-control study.…”
Section: Assessment Of the Outcome After Sclerotherapymentioning
confidence: 99%